Ocular Manifestations of Infectious Salmon Anaemia Virus Infection in Atlantic Salmon ( Salmo salar ) - Emily Mahon; Rebecca R. Kwabiah; Hélène Paradis; Manuel A. Soto‐Dávila; Sathees Duglas; Raja Ram Gurung; Thurka Paramanathan; Ignacio Vasquez; Shams Al‐Badoosh; John Law; Javier Santander; Mark D. Fast; et al. (Journal of Fish Diseases, 2026)
Eyes are essential sensory organs needed by teleost Atlantic salmon for high visual acuity and survival in both the wild and in aquaculture settings. In this work, we assessed the ocular manifestations of Infectious Salmon Anaemia Virus (ISAV) infection in Atlantic salmon by a cohabitation‐mediated infection assay and histological and immunohistochemical approaches. The findings reveal that Atlantic salmon with a systemic ISAV infection displayed ISAV antigen accumulation in specific ocular tissues and significant ocular morphological changes that could compromise visual acuity. Immunohistochemical analyses showed that ISAV‐related ocular pathological changes correlate with changes in expression levels and/or spatial localizations of IgM, Sox6, Sox9, collagen type 1, Gata1, and CD10 in specific compartments of the eye. The cornea is likely one of the first ocular tissues to be exposed to the cohabitation‐mediated ISAV infection. The ISAV‐infected Atlantic salmon showed corneal dysplasia, which correlated with increased corneal stromal ISAV antigen expression, dysregulated IgM, Sox6, and collagen type 1 expression, and an induction of Sox9 expression at the corneal surface. The choroid rete mirabile of ISAV‐infected eyes showed a decreased complement of erythrocytes, consistent with anaemia, while Gata1 expression, a key mediator of erythropoiesis, was upregulated compared to non‐infected eyes, suggesting a potential erythropoietic compensatory response. These findings provide a basis for further study of ISAV‐mediated ocular pathological changes and new insight into the pathogenesis of orthomyxoviruses in the eye.